Breaking Bad and Better Call Saul: Struggling and Living in Liquid Times. - Pierson, David (Canadian Review of American Studies)
AMC's TV series Breaking Bad and Better Call Saul both feature protagonists who can be seen as victims of institutions that do not appreciate their talents and abilities. Walter White in Breaking Bad, who once won a Nobel Prize in chemistry, is an under-appreciated and underpaid high school chemistry teacher who must work a second job to support his family. Jimmy McGill, a con artist–turned–lawyer who will eventually change his identity to Saul Goodman in Better Call Saul discovers that because of his earlier criminal exploits and non-traditional legal education, he will never be fully accepted within Albuquerque's legal community. These series exemplify several core concepts from Zygmunt Bauman and Martin Shuster's works, including liquid modernity and late capitalism, the loss of normative authority and deinstitutionalization, the process of individuation and identity formation, and the centrality of family in living and struggling in liquid times.